The effectiveness of games in group guidance in improving students’ interpersonal relationships - Loban, Maria Natalia (Konselor, 2020)
This research aimed to determine the effectiveness of games in group guidance in improving students' interpersonal relationships. Games that were used were adapted to certain aspects of interpersonal relationships. An experimental method was used in this research, specifically the pre-experimental design: one group pre-test post-test. The effectiveness test was done by comparing the results of pre-test and post-test. The treatments were given to one group only without a comparison group. The hypothesis testing was done using non-parametric statistics, namely the Wilcoxon Statistical Test. The results showed an increase in students' interpersonal relationships through the provision of games in group guidance. The increased interpersonal relationships was by 17.2% and seen in all aspects of interpersonal relationships. Thus, it can be concluded that games in group guidance have proven to be effective in improving students' interpersonal relationships.